If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -3)(-2x + -5) = 0 Reorder the terms: (-3 + 5x)(-2x + -5) = 0 Reorder the terms: (-3 + 5x)(-5 + -2x) = 0 Multiply (-3 + 5x) * (-5 + -2x) (-3(-5 + -2x) + 5x * (-5 + -2x)) = 0 ((-5 * -3 + -2x * -3) + 5x * (-5 + -2x)) = 0 ((15 + 6x) + 5x * (-5 + -2x)) = 0 (15 + 6x + (-5 * 5x + -2x * 5x)) = 0 (15 + 6x + (-25x + -10x2)) = 0 Combine like terms: 6x + -25x = -19x (15 + -19x + -10x2) = 0 Solving 15 + -19x + -10x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + -5x)(5 + 2x) = 0Subproblem 1
Set the factor '(3 + -5x)' equal to zero and attempt to solve: Simplifying 3 + -5x = 0 Solving 3 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 0 + -3 -5x = 0 + -3 Combine like terms: 0 + -3 = -3 -5x = -3 Divide each side by '-5'. x = 0.6 Simplifying x = 0.6Subproblem 2
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5Solution
x = {0.6, -2.5}
| (2x-3)(x)=54 | | 3a+2=a+8 | | [(8x+21)+(5x+63)]+2y=360 | | (8x+21)+(5x+63)+2y=360 | | 6(x+2)(x-4)= | | 8x+21=5x+63 | | (n+2)*8=24 | | (n-5)*5=10 | | 10x-9=101 | | 30+63+2x+7=180 | | x^2+7+1=0 | | 2(3a+b)-6(2a-3b)= | | (n+1)*9=27q | | (n-4)*6=12 | | 148-2x=25x+19 | | 7-9x=83-23x | | x*x+7x=12 | | a*8+6=3 | | 8(x+2)=4(x+10) | | 4x-5=72-7x | | 152-10x=9x+19 | | 8x+5=3x+0 | | 11x+30=2x+300 | | 230-3x=42+20 | | 6x-9=-33-8x | | -3xy*2xy= | | 79-4x=8x-19 | | 6x^2-15x+8=0 | | x^2-8x+10=-2x+2 | | x^2-7x+15=9 | | 10x-17=14x-61 | | 3-t=3t+2 |